STUDYING MID-RANGE PLANAR ORBITS AROUND PHOBOS - Cavalca, M. P. O.; Prado, A. F. B. A.; Formiga, J. K. S. [UNESP]; Gomes, V. M. [UNESP]; Sanchez, D. M. (Univ Nacional Autonoma Mexico, Inst De Astronomia, 2018)
The goal of the present paper is to search and study mid-range planar orbits for a spacecraft traveling near Phobos. The first step is to make a numerical search and classification of natural orbits based in the concept of Quasi Satellite Orbits (QSO). The effects of the eccentricity of Phobos and the irregular shape of the bodies involved (Mars and Phobos) are studied, identifying the importance of these terms. This study is made using two different initial locations for Phobos, the periapsis and apoapsis. The results show the existence of several solutions, mapping the minimum, maximum and averaged Phobos-spacecraft distances.
Keywords: Words: celestial mechanics; planets and satellites: dynamical evolution and stability